1) Completa la tabla y representa la gráfica resultante:
x | 1 | 2 | 3 | 4 | 5 | 6 | 7 |
---|---|---|---|---|---|---|---|
y = x - 3 |
2) Completa la tabla y representa la gráfica resultante:
x | - 4 | - 3 | - 2 | - 1 | 0 | 1 | 2 |
---|---|---|---|---|---|---|---|
y = x + 5 |
3) Completa la tabla y representa la gráfica resultante:
x | - 2 | - 1 | 0 | 1 | 2 |
---|---|---|---|---|---|
y = 3x |
4) Completa la tabla y representa la gráfica resultante:
x | - 2 | - 1 | 0 | 1 | 2 |
---|---|---|---|---|---|
y = x2 - 1 |
No hay comentarios.:
Publicar un comentario